The Evolution of Comparative Administrative Law Studies - Kusiak-Winter, Renata (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The nature and scope of comparative studies is traditionally determined by the unique character of administrative law with its high rate of inward looking elements accounting for the characteristics of different states. Comparative studies are also flexible (variable) and fragmentised by nature. These two qualities appear to remain valid but the insular characteristics have been largely reduced as a result of loosening the ties of the administration with the state. This consequently influences comparative studies as we may draw a clear dividing line between the research on independent legal orders in the phase of no connections among the states and the phase of a high degree of interdependence and interaction among the legal orders in the membership framework of supranational organisations such as European Union. The aim of this paper is to show the complex premises applied in comparative studies of administrative law and discuss the needs specific to academic research and practical applications – the legislature, the judiciary and the executive. I will demonstrate that the research on comparative law has significantly changing its functions over the years, but it has made a permanent contribution to a deeper reflection on applicable law.
Keywords: studia porównawcze; prawo administracyjne